The Influence of Employee Experience on Employee Performance with Turnover Intention as a Mediating Variable among Employees WITH Generation at PT. Shou Fong Lastindo in Bojonegoro - Fadila Bernika Anastasia; Nurcholis Setiawan (Jurnal Riset Ekonomi, Manajemen, dan Bisnis, 2025)
This study examines the impact of employee experience on employee performance, with turnover intention as a mediating variable, among Generation Z employees at PT. Shou Fong Lastindo in Bojonegoro. This research employs a quantitative, survey-based approach, collecting data from 51 respondents via questionnaires. The analysis is conducted using Structural Equation Modeling (SEM). The findings indicate that employee experience has a significant positive effect on employee performance and on turnover intention. Furthermore, turnover intention positively affects employee performance and does not mediate the relationship between employee experience and performance. These results highlight the importance of enhancing employee experience to reduce turnover intention and improve employee performance. Organizations should focus on creating a supportive work environment, encouraging career development opportunities, and ensuring job satisfaction to retain Generation Z employees.